Antibiotics Wastewater Treatment - Elmolla, E. S.; Chaudhuri, M. (2008)
Antibiotics are emerging contaminants in the aquatic environment because they have adverse effects on aquatic life and humans. The problem created by the presence of antibiotics at low concentrations in the environment is the development of antibiotic resistant bacteria. This paper aims at giving a review of antibiotics wastewater treatment. Different advanced oxidation processes (AOPs), such as Fenton, photo-Fenton and ozonation have been applied as pretreatment of antibiotics wastewater. AOP pretreatment can reduce organic concentration and improve biodegradability. Biological treatment, both aerobic and anaerobic systems, have also been used for treatment of antibiotics wastewater, The treatment of antibiotic wastewater by biological systems is influenced by type and concentration of the antibiotic (active substance) in wastewater. Application of other AOPs pretreatment and biological treatment for different types of antibiotics wastewater is a challenging area of research.